Production of electrical power through hydraulic energy and its environmental impacts - Queiroz, Rosemar de; Koppe, Ezequiel; Grassi, Patricia; Tartas, Bruna; Lazzare, Kariane; Bozzetto, Cristiane; Kemerich, Pedro Daniel da Cunha (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611709124 This paper aimed makes a bibliographic review of how the electric energy is generated by hydropower plants and the environmental injuries by this kind of enterprise. The hydraulic energy is produced through the power of water movement, by hydropower plants. The main factors that influence the generation of this energy are: river’s flow, quantity of available water in a determined period of time and the difference in level, being them naturals, like waterfalls, or created artificially. Although of a significantly portion of contribution in world energy matrix, hydraulic energy causes several socioeconomic impacts, as great areas waterlogging injuring flora, fauna and the community that lives around the river. However this impacts are important whereas can be easily corrected, with a good environmental and social assistance, and a part of the investment coasts destined to it. Before the implantation of this enterprise, it’s important make and action plan aiming reduce the impacts caused.